Bimbingan Teknis Manajemen Keuangan Kelompok Usaha Bersama (KUB) Kelurahan Jaya Mekar - Nugroho, Gatot Wahyu (PT. Alahyan Publisher Sukabumi, 2023)
Technical guidance on KUB financial management is one solution to the problems faced by KUB members, namely the lack of understanding related to the basic principles of financial management, practical steps in financial planning and management, and the implementation of technology to support accurate financial recording and reporting. The purpose of this activity is to increase the understanding to MSMEs of KUB members regarding accurate financial reporting. The method of implementing this activity is technical guidance to MSME members of KUB Kelurahan Jaya Mekar. The partner in this bimtek activity is Lurah Keluraha Jaya Mekar. The evaluation was carried out by giving questionnaires to the participants before and after the delivery of the material, and the result was that the comprehension ability of the participants increased by 41%.